Quantification of Quality Improvement in Wheat Seed Processing - Doshi, J. S.; Patel, V. B.; Patel, J. B.; Patel, J. A. (Journal of Agricultural Engineering, 2014)
Wheat seed quality improvement through basic processing machines was investigated and quantified. It was observed that consistent seed quality could be achieved by efficient use of processing machines viz. air screen cleaners (seed pre-cleaner and seed grader) and specific gravity separator (SGS), irrespective of initial quality of the seed lot. The product and reject of these machines were evaluated for seed quality parameters. The physical purity of wheat seed (8.8 % w. b.) lot was upgraded from 97.72% to 99.56%, and germination was improved from 79.8% to 85.3%, which made the seed lot acceptable as per the Indian Minimum Seed Certification Standards. Other seed quality parameters viz. test weight (36.76 g to 40.88 g), germination index (18.70 to 20.74), vigour index - I (1317 to 1650) and vigour index - II (98.56 to 112.77) were also improved. Air screen machines were found effective in improving physical purity and specific gravity separator improved the germination and vigour of the wheat seed lot.